Adsorption characteristics of bovine serum albumin and rifampicin on immobilized metal ion affinity mesoporous adsorbents - Mustaffa, Azizul Azri; Kamarudin, Khairul Sozana Nor; Mat, Hanapi (Penerbit UTM Press, 2008)
Bovine serum albumin and rifampicin adsorption are studied by using MCM-41 and SBA-15 immobilized with metal ion, Cu2+, Ni2+ and Co2+ during their synthesis as the adsorbents. Batch equilibrium adsorption experiment were carried out to study the effect of the solution pH, types of adsorbents, types of metal immobilized on the mesoporous adsorbents and metal loading concentration on adsorption capacity. Buffered BSA and rifampicin was contacted with the adsorbents, shaken and centrifuged. BSA and rifampicin concentration was determined by UV/Vis spectrophotometer while adsorbate-adsorbent interactions were determined by Fourier Transform Infrared (FTIR). The adsorption capacity of BSA was highest at pH 4 near the pI of BSA at 4.9 while rifampicin uptake was maximum at pH 7 near the pKa2 of rifampicin. This is due to electrostatic attraction between proteins and surface of adsorbents. It was found that cationic form of rifampicin exhibited very high degree of adsorption with the cationic exchanger of adsorbents. Immobilization of metal ions into mesoporous framework has proven to increase the adsorption rate of BSA and rifampicin, and metal ions with different concentration also gave some influence to the adsorption capacity.